ANALISIS SPASIAL PERUBAHAN TUTUPAN LAHAN DI RESORT WATUMOHAI DAN RESORT MENDOKE UNTUK MENDUKUNG PENGELOLAAN TAMAN NASIONAL RAWA AOPA WOTUMOHAI (TNRAW) - Zulkarnain Zulkarnain; Alif Hudan Hudan; Halili Halili (BioWallacea : Jurnal Penelitian Biologi (Journal of Biological Research), 2016)
ABSTRACTThis Research aim to know the change of the land cover that happened from year 2005 until 2015 in Watumohai Resort and Mendoke Resort at the RawaAopa National Park Watumohai (TNRAW). Approach method in collecting data is geographical information system technology and remote sensing for used to the stocktaking of data, covering to identify and spreading allocation by spatial and supported with direct survey of data in the camp. Gathering pass field survey constructively map which have been made by result of the map overlay that closing of existing farm. This data collecting aim to note the field physical nature and correct data result secondary of identifying satellite image, and also other maps with situation of research location. The Result of this research indicate that of land cover in Watumohai Resort and Mendoke Resort that is a primary forest, secondary forest, dry farming agriculture, rice, savannah and open farm. The highert degradation of land cover’s natural during10 year that is primary forest for the width of 3.766,93 Ha (20,45%), secondary forest increase for the width 2.443,50 Ha (13,27%), dry farm agriculture increase for the width of 1.128,33Ha (6,13%), rice field increase for the width of 180,87 Ha (0,98 %)and savannah decrease for the width of 13,22 Ha (0,07%).Keyword : Land Cover, Spatial Analysis, Rawa Aopa National Park Watumohai                   (TNRAW).